SUN-611 Impact of Existing Heart Failure on Outcomes of Hospitalization of Hyperosmolar Hyperglycemic State. From the National Inpatient Sample - Ahmed, Fatima (J Endocr Soc, 2020)
Introduction: Patients with underlying heart failure (HF) are at increased risk for hyperosmolar hyperglycemic state (HHS). However, no studies have investigated whether the presence of existing HF would impact the outcomes of HHS. Objective: we aimed to study the impact of heart HF on outcomes of HHS among adult patients hospitalized for HHS. Methodology: The National Inpatient Sample (NIS) was queried for all patients who were admitted with a diagnosis of hyperosmolar hyperglycemic state during the years 2005-2014. The primary outcomes of the study were all-cause mortality, acute myocardial infarction (MI), acute stroke. The secondary outcomes were acute kidney injury (AKI), rhabdomyolysis, acute respiratory failure (ARF), need for mechanical ventilation (MV), length of stay (LOS), and total cost of stay. Results: Overall, 188,725 patients were admitted for hyperosmolar hyperglycemic state. Mean age was 55.9 (SEM: 0.1). Females were (43.9%), Caucasians were 37.4% while African American were 35.2%. Total mortality was 1.1%, MI was 1.3% and stroke was 1.1%. Most common secondary outcome was AKI seen in 31.3% followed by ARF seen in 2.9% of total. The mean cost was 7887 $ (SEM: 84.6) and mean LOS was 4.1 days (SEM: 0.03). Patients with heart failure had higher rates for mortality 2% vs 0.9%, p<0.001, MI 3.1% vs 1.1 % p<0.001 and stroke 1.6% vs 1%, p<0.001. In addition, they had higher rates for AKI, ARF, need for mechanical ventilation, length of stay and cost. No significant difference on risk for rhabdomyolysis. On multivariable analysis, patients with heart failure had higher odds for mortality adjusted odd’s ratio (a OR) 1.58 [95%CI: 1.15-2.17] p<0.01 and higher risk for stroke a OR 1.43 [95%CI:1.04-1.95] p=0.03. In addition, presence of heart failure significantly correlated with ARF, need for mechanical ventilation, higher cost and longer LOS. No significant association was demonstrated between heart failure and risk for Rhabdomyolysis, MI and AKI. Conclusion: Diabetic patients with heart failure who develop hyperosmolar hyperglycemic state are at higher risk for stroke and mortality and respiratory failure. Particular attention on fluid balance as well as early recognition for signs of stroke is warranted.